Relationship between Nucleus Swelling and Development Competence of Bovine Cloned Embryos Reconstructed by Enucleated Oocytes with Serum-starved or Serum-fed Fetal Somatic Cells - Mokhamad Fahrudin; Ni Wayan Kurniani Karja; Tatsuyuki Suzuki (Universitas Gadjah Mada, 2005)
This study was conducted to examine the occurrence of nuclear remodeling (nucleus swelling) and its effects on the subsequent in vitro development of bovine embryos reconstructed by serum-starved and serum-fed somatic cells. Results from this study demonstrated that all of the reconstructed embryos that received serum-starved and serum-fed somatic cells exhibited condensed-nuclei. More than 90% of the transferred nuclei exhibited nuclear envelope breakdown and premature chromatin condensation which clearly distinct from an intact nucleus. There was no significant difference on the degree of nucleus swelling in SS-NT embryos or SF-NT embryos, indicating that either serum-starved or confluent somatic cell lines could be reprogrammed by the recipient cytoplasm environments in similar pattern. Although the fusion rate was not significantly different among the groups, the proportion of SS-NT embryos which developed to the 2- to 4-cell stage (89.7%) and to the 8- to 16-cell stage (74.7%) was significantly higher than that of SF-NT embryos. Whereas, the proportion of reconstructed embryos that developed to the morula and blastocyst stages were not significantly different among the groups. Results of these studies demonstrate that reconstructed embryos, which received either serum-starved or serum-fed confluent somatic cells, showed similar developmental competence to the blastocyst stage.